1983
DOI: 10.1203/00006450-198309000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic and Jet Aerosolization of Phospholipids and the Effects on Surface Activity

Abstract: Summarytive dose theraw might be beneficial in the treatment of RDS, Surface active aerosols were produced from aqueous dispersions of mixed lipids (CLL), extracted fnnn bovine lung lavage. Particle size distributioas were measured as a funetion of humMity far two types of aerosol generators: ultrrrsoaif and jet. Lipid dispersions betore aerosolhation were prepared by sonication in an ice bath and by mechanical vortexing. Over a range of bigh huaddity greater than 60-70%, ultrasonic nebulization gave CLL leros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…This is about the same as the endogenous pool size of surfactant in newborn immature lambs that breathed well enough to avoid hypercapnia [23]. In a study by Marks et al [24], the amount of surfactant needed to cover the alveolar surface with a close-packed monolayer was calculated to be 3.1 mg·kg -1 . However, there is no evidence that such small amounts can have a clinical effect when delivered by inhalation.…”
Section: Discussionmentioning
confidence: 88%
“…This is about the same as the endogenous pool size of surfactant in newborn immature lambs that breathed well enough to avoid hypercapnia [23]. In a study by Marks et al [24], the amount of surfactant needed to cover the alveolar surface with a close-packed monolayer was calculated to be 3.1 mg·kg -1 . However, there is no evidence that such small amounts can have a clinical effect when delivered by inhalation.…”
Section: Discussionmentioning
confidence: 88%
“…Typical doses of intratracheal surfactant in premature infants are 100 mg/kg body weight. This represents a significant excess over the amount of surfactant phospholipid needed to cover the surface of the alveolar network with a tightly packed surfactant film (only about 3 mg/kg of surfactant phospholipid at a molecular weight of 750 Daltons are needed to form a monomolecular film at a limiting area of 40 Å 2 /molecule over an alveolar surface of 1 m 2 /kg body weight [46,150]). Excess instilled exogenous surfactant that reaches the alveoli provides a reservoir of material for the hypophase and interface, and is available for incorporation into endogenous surfactant pools via recycling pathways.…”
Section: Delivery Methods and Dosages For Exogenous Surfactant Therapmentioning
confidence: 99%
“…In theory, aerosolization could significantly reduce required surfactant doses, since delivery can be targeted to the alveoli by controlling particle size. Phospholipid aerosols with stable particle sizes appropriate for alveolar deposition in normal lungs can be formed by ultrasonic or jet nebulization [150,156,157], and exogenous surfactants have been aerosolized to animals and patients with surfactant deficiency or dysfunction [91,105,110,136,[158][159][160]. However, the theoretical potential of aerosols to improve alveolar deposition and reduce required surfactant doses has not been replicated in practice.…”
Section: Delivery Methods and Dosages For Exogenous Surfactant Therapmentioning
confidence: 99%
“…157,158,173 Aero-sol delivery to the alveoli in normal lungs is maximal in the particle-size range 0.5-2.0 m, and it is possible to generate a stable surfactant aerosol with that particle size range from aqueous or powdered surfactant. 135,174,175 A recent study by Ruppert et al 135 demonstrated the ability to deliver substantial amounts of a powder recombinant protein C surfactant aerosol with a new aerosol generator to improve oxygenation and compliance in lung-lavaged rabbits. However, whether surfactant aerosolization can be accomplished in a sufficiently effective and efficient manner to replace instillation requires further and more detailed direct comparisons in animals and subsequently in human trials.…”
Section: Animal Studies Of Surfactantmentioning
confidence: 99%